2016
DOI: 10.1586/1744666x.2016.1171143
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D in atopic dermatitis, chronic urticaria and allergic contact dermatitis

Abstract: Summary Vitamin D influences allergen-induced pathways in the innate and adaptive immune system, and its potential immunomodulatory role in allergic skin disorders has been explored. This comprehensive review article provides an overview of the role of vitamin D in three common dermatologic conditions: atopic dermatitis (AD), chronic urticaria, and allergic contact dermatitis (ACD). Whereas the literature regarding vitamin D and AD has resulted in mixed findings, several studies have described an inverse relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
3

Year Published

2016
2016
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 72 publications
1
28
0
3
Order By: Relevance
“…Similarly, an inverse correlation was found between maternal 25OHD levels and the development of eczema and asthma in children and, in adults, between 25OHD and asthma in the NHANES survey . The majority, although not all, of studies have shown an inverse correlation between 25OHD and atopic dermatitis . RTCs have not been plentiful, large, or consistent, although a meta‐analysis of four trials with vitamin D supplementation in atopic dermatitis demonstrated benefit …”
Section: Immune System and Immunologic Diseasesmentioning
confidence: 98%
“…Similarly, an inverse correlation was found between maternal 25OHD levels and the development of eczema and asthma in children and, in adults, between 25OHD and asthma in the NHANES survey . The majority, although not all, of studies have shown an inverse correlation between 25OHD and atopic dermatitis . RTCs have not been plentiful, large, or consistent, although a meta‐analysis of four trials with vitamin D supplementation in atopic dermatitis demonstrated benefit …”
Section: Immune System and Immunologic Diseasesmentioning
confidence: 98%
“…Neuere Untersuchungen weisen darauf hin, dass auch Vitamin D, welches nach UV-Bestrahlung in der Haut gebildet wird, mit dem atopischen Ekzem in Zusammenhang steht. In der Literatur sind bis heute zahlreiche Studien zu finden, die entweder eine inverse Assoziation, eine direkte Assoziation und auch keine Assoziation zwischen dem 25-OH-Vitamin-D-Status und einer atopischen Dermatitis zeigen [11]. Jedoch zeigt die überwiegende Zahl der Studien eine schützende Bedeutung von Vitamin D bei Patienten mit atopischer Dermatitis.…”
Section: Umwelt Und Mikrobiomunclassified
“…Poole et al [19] in their study conducted on infants showed that vitamin D insufficiency is associated with an increased risk of a challenge-proven peanut/egg allergy. Quirk et al [20] suggest that vitamin D deficiency increases the risk of sensitization to food allergens, particularly to milk and wheat. In our study, we found a statistically significant correlation between nettle rash and comorbidity asthma (with one or more allergic diseases) and lower mean vitDs level (p = 0.005), which we consider to be interdependence.…”
Section: Discussionmentioning
confidence: 99%